Highly Pathogenic Avian Influenza Clade 2.3.4.4 Subtype H5N6 Viruses Isolated from Wild Whooper Swans, Mongolia, 2020 - Jeong, Sol (Emerg Infect Dis, 2021)
We identified clade 2.3.4.4 highly pathogenic avian influenza A(H5N6) viruses from whooper swans (Cygnus cygnus) found dead in Mongolia. The identification of these infections in wild birds in this area is of concern because of the potential for virus dissemination during fall migration.